2017
DOI: 10.1161/jaha.116.004585
|View full text |Cite
|
Sign up to set email alerts
|

Vinexin β Ablation Inhibits Atherosclerosis in Apolipoprotein E–Deficient Mice by Inactivating the Akt–Nuclear Factor κB Inflammatory Axis

Abstract: BackgroundVinexin β is a novel adaptor protein that regulates cellular adhesion, cytoskeletal reorganization, signal transduction, and transcription; however, the exact role that vinexin β plays in atherosclerosis remains unknown.Methods and ResultsImmunoblot analysis showed that vinexin β expression is upregulated in the atherosclerotic lesions of both patients with coronary heart disease and hyperlipemic apolipoprotein E–deficient mice and is primarily localized in macrophages indicated by immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In recent years, with the deepening of the research, the MIP-1 α effect on the tumor microenvironment has gradually transferred to cardiovascular diseases. MIP-1 α can be utilized to predict clinical outcomes in patients with atherosclerotic cardiovascular disease, myocardial ischemia, and heart failure [ 13 ]. In cardiac-specific transgenic mice [ 14 ], the CCR9 and CCL3 overexpression enhanced pressure overload-induced cardiac hypertrophy; CCL3 and CCL4 levels were higher in the hearts of transverse aortic stenosis mice compared with sham-operated mice.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the deepening of the research, the MIP-1 α effect on the tumor microenvironment has gradually transferred to cardiovascular diseases. MIP-1 α can be utilized to predict clinical outcomes in patients with atherosclerotic cardiovascular disease, myocardial ischemia, and heart failure [ 13 ]. In cardiac-specific transgenic mice [ 14 ], the CCR9 and CCL3 overexpression enhanced pressure overload-induced cardiac hypertrophy; CCL3 and CCL4 levels were higher in the hearts of transverse aortic stenosis mice compared with sham-operated mice.…”
Section: Discussionmentioning
confidence: 99%
“…SORBS3 encodes an SH3 domain-containing adaptor protein that regulates cell adhesion and signal transduction. The deficiency of adaptor protein could suppress vascular inflammation and inactivate Akt–nuclear factor κB signaling [ 32 ]. IGHV1S18 is an immunoglobulin heavy chain variable region that encodes Ig heavy chain and is directly related to the formation of immunoglobulins.…”
Section: Discussionmentioning
confidence: 99%
“…Next, to further assess the molecular mechanisms underlying the effects of MTMR14, we tested the downstream pathways involved in MTMR14-mediated CH pathogenesis. Since the Akt signaling pathway has emerged as an essential intracellular pathway in CH, particularly AKT/GSK3β/mTOR pathways as regulators of CH [15][16][17] , we first studied the potential involvement of Akt signaling pathways in the pro-hypertrophic role of MTMR14. The Western blotting results showed that the phosphorylation levels of Akt, GSK3β, mTOR, and p70-S6K were significantly increased in hypertrophic hearts in MTMR14-CKO mice compared with the hearts of MTMR14-Flox controls subjected to AB surgery (Fig.…”
Section: Mtmr14 Inhibits Akt Signaling In the Pathogenesis Of Chmentioning
confidence: 99%